Efficient use of energy in buildings—New smart trends - (:unkn) unknown (Springer, 2020)
Depletion of the fossil fuels which provide most of the world’s energy demand today, increase in the consumption in industrial processes and the rise in the concentration of greenhouse gases in the atmosphere to dangerous levels to human health as a result of the destruction of the ozone layer, have put energy supply and efficient use of energy among the most challenging topics today. Energy saving and the efficient use of energy are becoming more and more important. World states and international organizations are competing with each other to access energy resources (oil, natural gas, coal…). Energy is the infrastructure of industrialization and an indispensable element of daily life. Therefore, the need for energy occupies an important place in the national and international agenda. Due to the depletion of energy resources, the existence of external dependence and environmental impacts; producing safe, sufficient amounts of cheap and clean energy for countries is among the main problems of economic and social life today. Our country is growing rapidly with its industry, economy and population. For this reason, it is of great importance to use the generated energy with high efficiency and to evaluate the potential of alternative and renewable energy sources as well as the existing energy sources. The key issue to a sustainable development is the balance between the supply and demand of energy, keeping the environment clean, healthy and pollutant free. Energy efficiency is the reduction of energy consumption per unit or product amount without causing a decrease in the quality of life and quality of services in buildings and production quality and quantity in industrial enterprises. Buildings are responsible for about a third of the global energy consumption. Especially in developing countries like Turkey, during the rapid urban transformation in renovated buildings, energy performance should also be given importance as well as earthquake-resistance. Energy performance of buildings should be sustainable. In this context, smart buildings represent an important stage of energy efficiency and constitute the basic element of the smart micro grid. Large amounts of data must be stored and processed during the planning, implementation, control and correction cycle of air conditioning and mechanical systems. To ensure energy efficiency in buildings, a network structure consisting of wireless sensors and micro control elements is used. This chapter focuses on the new trends in smart buildings. © Springer Nature Switzerland AG 2020.
Keywords: Efficiency; Energy; Energy performance of buildings and industry; Energy performance software